Analisis Kinerja Alat Bor dalam Penyediaan Lubang Ledak untuk Mencapai Target Produksi Pembongkaran Overburden di Pit.7 PT. Insani Bara Perkasa Kabupaten Kutai Kertanegara Provinsi Kalimantan Timur - Muh. Iskandar Rahman; Revia Oktaviani; Agus Winarno; Tommy Trides; Albertus Juvensius Pontus (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
Blast hole drilling is an initial stage that plays a critical role in determining the success of blasting activities in mining and construction operations. Drilling quality directly affects rock fragmentation, drilling equipment efficiency, drilling equipment productivity, as well as blasting safety and costs. This study aims to analyze the influence of drilling parameters on blast hole quality, including hole diameter, drilling depth, hole inclination, and the suitability of drilling patterns with respect to the planned blasting design. The research methodology involves field observations, actual measurements of drill holes, and analysis of data obtained from drilling and blasting productivity. The results show that deviations in hole depth and direction can lead to irregular distribution of blasting energy, resulting in suboptimal rock fragmentation and an increased potential for flyrock and overbreak. In addition, the selection of appropriate drilling methods and equipment based on rock mass characteristics has been proven to improve productivity and blast hole quality. Therefore, controlling drilling parameters and implementing proper operational procedures are essential to enhance the overall effectiveness and productivity of blasting activities. This study is expected to serve as a reference for the planning and evaluation of blast hole drilling activities to achieve more efficient, safe, and economical operations.